Adverbial Clauses in Dumi - Rai, Netra Mani (Nepalese Linguistics, 2024)
This paper outlines the distribution of adverbial clauses in Dumi, a minority indigenous language among 26 Kirati Rai languages in Nepal. It has used secondary data based on Rai (2017). The primary data include the narrative with Dumi speakers from the Makpa area of the Dumi homeland and the writer's intuition as a mother tongue speaker. This study shows that the adverbial subordinate clauses in Dumi are either marked by the subordinating morphemes attached to the verb of the dependent clause or by the presence of the non-finite verb forms. Temporal adverbial clauses include precedence, subsequence and simultaneous in Dumi.